A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

The performance of shared suction caisson anchors in sand for floating offshore wind arrays with taut and catenary mooring - James Barron; Edward Land; Mohamed Rouainia; Tom Charlton; Fraser Gibson; Stuart Edwards (Ocean Engineering, 2026)

Prevalence of traded bird species in key biodiversity areas - Oscar Morton; Tom Lansley; Stuart H. M. Butchart; Graeme M. Buchanan; David P. Edwards (Conservation Biology, 2026)
The use and trade of biodiversity involve tens of thousands of species that are exploited at a range of scales, intensities, and degrees of sustainability. As a result, some are highly threatened. Key biodiversity areas (KBAs) are sites of significance for the persistence of biodiversity identified nationally based on standardized criteria. The degree to which biodiversity in KBAs is likely to be used and traded is not well understood. We undertook a fine‐scale assessment of the area of habitat (AOH) of traded species in KBAs. We used data on >16,000 KBAs and combined these with AOH maps for >10,000 bird species, a heavily traded and well‐documented indicator taxon. We subsequently mapped and quantified the distribution of traded species richness, extinction risk, and range‐size rarity in and adjacent to KBAs. Although less than half of all bird species are traded, we found that most bird species in KBAs were traded, and the richness of traded species was more than twice (119%) that of nontraded species. Traded species had comparable proportions of their AOH (22.5% on average) in KBAs as nontraded species (21.5%). Global hotspots of richness, extinction risk, and range rarity for traded species disproportionately occurred in KBAs, which had higher levels of extinction risk and range rarity for traded species than locations immediately outside KBAs. Of the 46 species that are likely threatened by unsustainable use and have the majority of their habitat falling within KBAs, we found that eight species had no habitat in designated protected areas. Reconciling sustainable use and the critical importance of KBAs for threatened species is essential. Our results suggest that for some species, there is an urgent need to protect key sites and ensure that any use and trade of species within them are sustainable.

Addressing how spatial resolution affects image velocimetry outputs: implications for measurements from space - Harley Dixey; Edward Rollason; Stuart Dunning; Matthew Thomas Perks (Hydrological Sciences Journal, 2026)

Deep learning-based plastic classification using spectroscopic data - Aru Ranjan Singh; Edward Ren Kai Neo; Car Man Lai; Sumit Hazra; Stuart Coles; Ton Peijs; Kurt Debattista (Journal of Cleaner Production, 2025)

Effectiveness of Key Biodiversity Areas in representing global avian diversity - Tom P. Lansley; Olivia Crowe; Stuart H. M. Butchart; David P. Edwards; Gavin H. Thomas (Conservation Biology, 2025)
Key Biodiversity Areas (KBAs) are the largest and most complete network of significant sites for the global persistence of biodiversity. Although important sites for birds worldwide have been relatively well assessed, a key question is how effectively the global KBA network represents avian diversity. We identified bird species, orders, habitats, and geographic regions that are underrepresented by KBAs. Area of Habitat (AOH) maps for 10,517 terrestrial bird species were cropped and masked by the extent of each KBA. Almost all species had at least one part of their seasonal distribution in one or more KBAs. Twenty‐nine species had no habitat overlap with KBAs, and 1900 species had 2 ). Terrestrial bird species of tropical forests were 12.8% better represented in KBAs than expected by chance, whereas boreal and temperate forest species were less well represented than expected by chance (74.4% and 25.1%, respectively). Among avian orders, Anseriformes and Charadriiformes were underrepresented in KBAs (29.0% and 17.9%, respectively), whereas Trogoniformes and Psittaciformes were better represented (16.2% and 6.9%, respectively) than expected by chance. Bird species for potential KBA identification include marsh antwren ( Formicivora paludicola ) and Tabar pitta ( Erythropitta splendida ). These are mainly due to recent changes in species’ taxonomy or their International Union for Conservation of Nature Red List category. Identifying poorly represented species and where they occur highlights shortfalls where expansion of the network could bring conservation benefits.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Quantifying impacts of sustainable transport interventions in Scotland: A system dynamics approach - Kathleen Davies; Edward Hart; Stuart Galloway (Transportation Research Part D: Transport and Environment, 2024)

Seismic performance of shared suction caisson anchors installed in liquefiable sand for floating offshore wind turbines - James Barron; Mohamed Rouainia; Tom Charlton; Stuart Edwards; Fraser Gibson (Soil Dynamics and Earthquake Engineering, 2024)

Closing the gap between existing large‐area imaging research and marine conservation needs - Orion S. McCarthy; Kanisha Contractor; Will F. Figueira; Arthur C. R. Gleason; T. Shay Viehman; Clinton B. Edwards; Stuart A. Sandin (Conservation Biology, 2024)
Emerging technology has immense potential to increase the scale and efficiency of marine conservation. One such technology is large‐area imaging (LAI), which relies on structure‐from‐motion photogrammetry to create composite products, including 3‐dimensional (3‐D) environmental models, that are larger in spatial extent than the individual images used to create them. Use of LAI has become widespread in certain fields of marine science, primarily to measure the 3D structure of benthic ecosystems and track change over time. However, the use of LAI in the field of marine conservation appears limited. We conducted a review of the coral reef literature on the use of LAI to identify research themes and regional trends in applications of this technology. We also surveyed 135 coral reef scientists and conservation practitioners to determine community familiarity with LAI, evaluate barriers practitioners face in using LAI, and identify applications of LAI believed to be most exciting or relevant to coral conservation. Adoption of LAI was limited primarily to researchers at institutions based in advanced economies and was applied infrequently to conservation, although conservation practitioners and survey respondents from emerging economies indicated they expect to use LAI in the future. Our results revealed disconnect between current LAI research topics and conservation priorities identified by practitioners, highlighting the need for more diverse, conservation‐relevant research using LAI. We provide recommendations for how early adopters of LAI (typically Global North scientists from well‐resourced institutions) can facilitate access to this conservation technology. These recommendations include developing training resources, creating partnerships for data storage and analysis, publishing standard operating procedures for LAI workflows, standardizing methods, developing tools for efficient data extraction from LAI products, and conducting conservation‐relevant research using LAI.

Total infectome investigation of diphtheritic stomatitis in yellow-eyed penguins (Megadyptes antipodes) reveals a novel and abundant megrivirus - Janelle R. Wierenga; Rebecca M. Grimwood; Harry S. Taylor; Stuart Hunter; Lisa S. Argilla; Trudi Webster; Lauren Lim; Rebecca French; Hendrik Schultz; Fátima Jorge; Mihnea Bostina; Laura Burga; et al. (Veterinary Microbiology, 2023)

Top ten priorities for global saltmarsh restoration, conservation and ecosystem service research - Julien Pétillon; Emma McKinley; Meghan Alexander; Janine B. Adams; Christine Angelini; Thorsten Balke; John N. Griffin; Tjeerd Bouma; Sally Hacker; Qiang He; Marc J.S. Hensel; Carles Ibáñez; et al. (Science of The Total Environment, 2023)

The importance of time-resolved personal Dosimetry in space: The ISS Crew Active Dosimeter - Ramona Gaza; A. Steve Johnson; Bryan Hayes; Thomas Campbell-Ricketts; Jani Rakkola; Mena Abdelmelek; Cary Zeitlin; Stuart George; Nicholas Stoffle; Andrew Castro; Clif Amberboy; Edward Semones (Life Sciences in Space Research, 2023)

Enrollment, retention, and inclusivity of Marine Stewardship Council (MSC) eco-labelling certifications - Stuart T. Jones; Edward H. Allison; Kailin Kroetz; Yoshitaka Ota; Sunny L. Jardine (Marine Policy, 2023)

Challenges in cybersecurity: Lessons from biological defense systems - Edward Schrom; Ann Kinzig; Stephanie Forrest; Andrea L. Graham; Simon A. Levin; Carl T. Bergstrom; Carlos Castillo-Chavez; James P. Collins; Rob J. de Boer; Adam Doupé; Roya Ensafi; Stuart Feldman; et al. (Mathematical Biosciences, 2023)

Cross-modal generative models for multi-modal plastic sorting - Edward R.K. Neo; Jonathan S.C. Low; Vannessa Goodship; Stuart R. Coles; Kurt Debattista (Journal of Cleaner Production, 2023)

Variability in composition of parrotfish bite scars across space and over time on a central Pacific atoll - Jonathan A. Charendoff; Clinton B. Edwards; Nicole E. Pedersen; Vid Petrovic; Brian Zgliczynski; Stuart A. Sandin; Jennifer E. Smith (Coral Reefs, 2023)
Parrotfishes are conspicuous herbivores, microvores, and detritivores in coral reef ecosystems, and the impacts of their feeding, particularly their capacity to expose reef carbonate, have received much attention. In many cases, parrotfish assemblages have been shown to control algal proliferation and promote the settlement of corals and crustose coralline algae (CCA). In extreme cases, high densities of parrotfishes may negatively affect net reef accretion through bioerosion and targeted coral predation. Most evidence describing the impacts of parrotfish foraging on benthic community structure is based upon correlations between benthic composition and parrotfish behavior or abundance, with much less known about process-based change of individual parrotfish bite scars through time. Here, we estimated parrotfish bite selectivity and determined the change in benthic composition within parrotfish bite scars relative to change in the overall reefscape using data collected over a 12-month duration from the fore reef habitat at Palmyra Atoll. We identified 2150 parrotfish bite scars which appeared most frequently on turf algae covered substrata but also on coral, CCA, and encrusting macroalgae. Of those bites taken on live coral, 96% of scars returned to live coral within 12 months. Notably, adult coral survivorship in bite scars was higher than at randomly sampled coral-covered locations not affected by parrotfish bites. The exposed substrate within bite scars was most commonly colonized by the dominant benthic functional group in the area immediately surrounding the scar. We found little evidence of coral recruitment to bite scars (1/2150); however, CCA growth on bites initially on turf algae increased from 18.4 to 32.9% across the two time intervals. Our results suggest that benthic areas affected by parrotfish bites were more likely to undergo a successional shift to a more calcified state relative to unaffected benthic areas, indicating that parrotfish grazing helps maintain highly calcified coral reef ecosystems.

Range and extinction dynamics of the steppe bison in Siberia: A pattern‐oriented modelling approach - July A. Pilowsky; Sean Haythorne; Stuart C. Brown; Mario Krapp; Edward Armstrong; Barry W. Brook; Carsten Rahbek; Damien A. Fordham (Global Ecology and Biogeography, 2022)
Aim To determine the ecological processes and drivers of range collapse, population decline and eventual extinction of the steppe bison in Eurasia. Location Siberia. Time period Pleistocene and Holocene. Major taxa studied Steppe bison ( Bison priscus ). Methods We configured 110,000 spatially explicit population models (SEPMs) of climate–human–steppe bison interactions in Siberia, which we ran at generational time steps from 50,000 years before present. We used pattern‐oriented modelling (POM) and fossil‐based inferences of distribution and demographic change of steppe bison to identify which SEPMs adequately simulated important interactions between ecological processes and biological threats. These “best models” were then used to disentangle the mechanisms that were integral in the population decline and later extinction of the steppe bison in its last stronghold in Eurasia. Results Our continuous reconstructions of the range and extinction dynamics of steppe bison were able to reconcile inferences of spatio‐temporal occurrence and the timing and location of extinction in Siberia based on hundreds of radiocarbon‐dated steppe bison fossils. We showed that simulating the ecological pathway to extinction for steppe bison in Siberia in the early Holocene required very specific ecological niche constraints, demographic processes and a constrained synergy of climate and human hunting dynamics during the Pleistocene–Holocene transition. Main conclusions Ecological processes and drivers that caused ancient population declines of species can be reconstructed at high spatio‐temporal resolutions using SEPMs and POM. Using this approach, we found that climatic change and hunting by humans are likely to have interacted with key ecological processes to cause the extinction of the steppe bison in its last refuge in Eurasia.

Benthic assemblages are more predictable than fish assemblages at an island scale - Stuart A. Sandin; Esmeralda Alcantar; Randy Clark; Ramón de León; Faisal Dilrosun; Clinton B. Edwards; Andrew J. Estep; Yoan Eynaud; Beverly J. French; Michael D. Fox; Dave Grenda; Scott L. Hamilton; et al. (Coral Reefs, 2022)
Decades of research have revealed relationships between the abundance of coral reef taxa and local conditions, especially at small scales. However, a rigorous test of covariation requires a robust dataset collected across wide environmental or experimental gradients. Here, we surveyed spatial variability in the densities of major coral reef functional groups at 122 sites along a 70 km expanse of the leeward, forereef habitat of Curaçao in the southern Caribbean. These data were used to test the degree to which spatial variability in community composition could be predicted based on assumed functional relationships and site-specific anthropogenic, physical, and ecological conditions. In general, models revealed less power to describe the spatial variability of fish biomass than cover of reef builders (R 2 of best-fit models: 0.25 [fish] and 0.64 [reef builders]). The variability in total benthic cover of reef builders was best described by physical (wave exposure and reef relief) and ecological (turf algal height and coral recruit density) predictors. No metric of anthropogenic pressure was related to spatial variation in reef builder cover. In contrast, total fish biomass showed a consistent (albeit weak) association with anthropogenic predictors (fishing and diving pressure). As is typical of most environmental gradients, the spatial patterns of both fish biomass density and reef builder cover were spatially autocorrelated. Residuals from the best-fit model for fish biomass retained a signature of spatial autocorrelation while the best-fit model for reef builder cover removed spatial autocorrelation, thus reinforcing our finding that environmental predictors were better able to describe the spatial variability of reef builders than that of fish biomass. As we seek to understand spatial variability of coral reef communities at the scale of most management units (i.e., at kilometer- to island-scales), distinct and scale-dependent perspectives will be needed when considering different functional groups.

Giant Tree Frog diversification in West and Central Africa: Isolation by physical barriers, climate, and reproductive traits - Kyle E. Jaynes; Edward A. Myers; Václav Gvoždík; David C. Blackburn; Daniel M. Portik; Eli Greenbaum; Gregory F. M. Jongsma; Mark‐Oliver Rödel; Gabriel Badjedjea; Abraham Bamba‐Kaya; Ninda L. Baptista; Jeannot B. Akuboy; et al. (Molecular Ecology, 2022)
Secondary sympatry amongst sister lineages is strongly associated with genetic and ecological divergence. This pattern suggests that for closely related species to coexist in secondary sympatry, they must accumulate differences in traits that mediate ecological and/or reproductive isolation. Here, we characterized inter‐ and intraspecific divergence in three giant tree frog species whose distributions stretch across West and Central Africa. Using genome‐wide single‐nucleotide polymorphism data, we demonstrated that species‐level divergence coincides temporally and geographically with a period of large‐scale forest fragmentation during the late Pliocene. Our environmental niche models further supported a dynamic history of climatic suitability and stability, and indicated that all three species occupy distinct environmental niches. We found modest morphological differentiation amongst the species with significant divergence in tympanum diameter and male advertisement call. In addition, we confirmed that two species occur in secondary sympatry in Central Africa but found no evidence of hybridization. These patterns support the hypothesis that cycles of genetic exchange and isolation across West and Central Africa have contributed to globally significant biodiversity. Furthermore, divergence in both ecology and reproductive traits appear to have played important roles in maintaining distinct lineages. At the intraspecific level, we found that climatic refugia, precipitation gradients, marine incursions, and potentially riverine barriers generated phylogeographic structure throughout the Pleistocene and into the Holocene. Further studies examining phenotypic divergence and secondary contact amongst these geographically structured populations may demonstrate how smaller scale and more recent biogeographic barriers contribute to regional diversification.

Post-settlement demographics of reef building corals suggest prolonged recruitment bottlenecks - Lauranne Sarribouette; Nicole E. Pedersen; Clinton B. Edwards; Stuart A. Sandin (Oecologia, 2022)
For many organisms, early life stages experience significantly higher rates of mortality relative to adults. However, tracking early life stage individuals through time in natural settings is difficult, limiting our understanding of the duration of these ‘mortality bottlenecks’, and the time required for survivorship to match that of adults. Here, we track a cohort of juvenile corals (1–5 cm maximum diameter) from 12 taxa at a remote atoll in the Central Pacific from 2013 to 2017 and describe patterns of annual survivorship. Of the 537 juveniles initially detected, 219 (41%) were alive 4 years later, 163 (30%) died via complete loss of live tissue from the skeleton, and the remaining 155 (29%) died via dislodgement. The differing mortality patterns suggest that habitat characteristics, as well as species-specific features, may influence early life stage survival. Across most taxa, survival fit a logistic model, reaching > 90% annual survival within 4 years. These data suggest that mortality bottlenecks characteristic of ‘recruitment’ extend up to 5 years after individuals can be visually detected. Ultimately, replenishment of adult coral populations via sexual reproduction is needed to maintain both coral cover and genetic diversity. This study provides key insights into the dynamics and time scales that characterize these critical early life stages.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Evolution of the African slippery frogs (Anura: Conraua ), including the world’s largest living frog - David C. Blackburn; Stuart V. Nielsen; Michael F. Barej; Joseph Doumbia; Mareike Hirschfeld; N’Goran G. Kouamé; Dwight Lawson; Simon Loader; Caleb Ofori‐Boateng; Edward L. Stanley; Mark‐Oliver Rödel (Zoologica Scripta, 2020)
Although Conraua goliath is well known as the largest living frog species, the diversity and evolution of the genus Conraua across sub‐Saharan Africa remain poorly understood. We present multilocus phylogenetic analyses of the six currently recognized species that provide insights into divergence times, biogeography, body size evolution and undescribed species. An analysis of divergence times demonstrates that crown‐group Conraua arose some time during the latest Oligocene to mid‐Miocene followed by divergence into major lineages in the mid‐Miocene that may reflect the fragmentation of widespread tropical forests in Africa that began at this time. We find three pairs of sister species, C. crassipes + C. beccarii , C. alleni + C. derooi and C. goliath + C. robusta , each of which diverged during the Miocene. These relationships reject phylogenetic hypotheses based solely on biogeography as the geographically peripheral C. beccarii from north‐eastern Africa is nested within western African species and the Central African species do not form a clade. Our species delimitation analyses provide support for undescribed species in C. alleni , C. beccarii and C. derooi , and possibly C. crassipes , suggesting that the current taxonomy substantially underestimates species diversity. There is no clear directional trend of either increasing or decreasing body size in Conraua and the three largest species do not form a clade. With a robust phylogenetic hypothesis in hand, further field‐based studies are needed to understand the evolution of morphology and life history in this charismatic African anuran clade.

Quantifying life history demographics of the scleractinian coral genus Pocillopora at Palmyra Atoll - Sho M. Kodera; Clinton B. Edwards; Vid Petrovic; Nicole E. Pedersen; Yoan Eynaud; Stuart A. Sandin (Coral Reefs, 2020)

A toxicity-based analysis of Canada’s National Pollutant Release Inventory (NPRI): a case study in Nova Scotia - Stephanie Taylor; Stuart Johnston Edwards; Tony R. Walker (Environmental Science and Pollution Research, 2020)

Changes in benthic community composition associated with the outbreak of the corallimorph, Rhodactis howesii, at Palmyra Atoll - Amanda L. Carter; Clinton B. Edwards; Michael D. Fox; Corinne G. Amir; Yoan Eynaud; Maggie D. Johnson; Levi S. Lewis; Stuart A. Sandin; Jennifer E. Smith (Coral Reefs, 2019)

Limited coral mortality following acute thermal stress and widespread bleaching on Palmyra Atoll, central Pacific - Michael D. Fox; Amanda L. Carter; Clinton B. Edwards; Yuichiro Takeshita; Maggie D. Johnson; Vid Petrovic; Corinne G. Amir; Enric Sala; Stuart A. Sandin; Jennifer E. Smith (Coral Reefs, 2019)

High‐turbidity events in Western Lake Erie during ice‐free cycles: Contributions of river‐loaded vs. resuspended sediments - Qianru Niu; Meng Xia; Stuart A. Ludsin; Philip Y. Chu; Doran M. Mason; Edward S. Rutherford (Limnology and Oceanography, 2018)
High‐turbidity events (HTEs) are common phenomena in shallow‐water environments that can alter ecological interactions. The relative contributions of river input (external loading) vs. resuspension (internal loading) to the occurrence, duration, and influenced areas of HTEs are not fully understood in most systems, owing to the lack of long‐term, source‐specified sediment maps. Using a Finite Volume Community Ocean Model‐based wave‐current forced sediment model, we investigated sediment dynamics in the shallow, river‐dominated Western Lake Erie during ice‐free cycles (April–November) of 2002–2012. Results indicated that wind waves predominated sediment dynamics in the offshore areas, with river discharges causing substantial inshore to offshore gradients. Owing to varying wind waves and river discharges, both the mean and extreme sediment dynamics had distinctive seasonal variations. The basin was turbid during spring and fall, with frequent (> 15%), broad (O [10 2 –10 3 km 2 ]), and more persistent (means of 3.2/4.4 d during spring/fall) HTEs caused mainly by resuspension events. During summer, the basin was clearer with occasional ( 2 km 2 ]), and short (mean of 1.5 d) HTEs near the mouths generated by pulsing river loadings. Although river loading rarely induced basin‐wide HTEs, they were important during floods, enlarging the high‐turbidity areas by 11.3%. Overall, by delineating the drivers of HTEs in Western Lake Erie, this study furthered the understanding of sediment dynamics in shallow ecosystems and provides a basis for investigating the ecological impact of sediments from different sources in river‐ and wave‐energetic systems.

Mapping of novel salt tolerance QTL in an Excalibur × Kukri doubled haploid wheat population - Muhammad A. Asif; Rhiannon K. Schilling; Joanne Tilbrook; Chris Brien; Kate Dowling; Huwaida Rabie; Laura Short; Christine Trittermann; Alexandre Garcia; Edward G. Barrett-Lennard; Bettina Berger; Diane E. Mather; et al. (Theoretical and Applied Genetics, 2018)
Key message Novel QTL for salinity tolerance traits have been detected using non-destructive and destructive phenotyping in bread wheat and were shown to be linked to improvements in yield in saline fields. Abstract Soil salinity is a major limitation to cereal production. Breeding new salt-tolerant cultivars has the potential to improve cereal crop yields. In this study, a doubled haploid bread wheat mapping population, derived from the bi-parental cross of Excalibur × Kukri, was grown in a glasshouse under control and salinity treatments and evaluated using high-throughput non-destructive imaging technology. Quantitative trait locus (QTL) analysis of this population detected multiple QTL under salt and control treatments. Of these, six QTL were detected in the salt treatment including one for maintenance of shoot growth under salinity ( QG (1 – 5) .asl - 7A ), one for leaf Na + exclusion ( QNa.asl - 7A ) and four for leaf K + accumulation ( QK.asl - 2B.1 , QK.asl - 2B.2 , QK.asl - 5A and QK:Na.asl - 6A ). The beneficial allele for QG (1 – 5) .asl - 7A (the maintenance of shoot growth under salinity) was present in six out of 44 mainly Australian bread and durum wheat cultivars. The effect of each QTL allele on grain yield was tested in a range of salinity concentrations at three field sites across 2 years. In six out of nine field trials with different levels of salinity stress, lines with alleles for Na + exclusion and/or K + maintenance at three QTL ( QNa.asl - 7A , QK.asl - 2B.2 and QK:Na.asl - 6A ) excluded more Na + or accumulated more K + compared to lines without these alleles. Importantly, the QK.asl - 2B.2 allele for higher K + accumulation was found to be associated with higher grain yield at all field sites. Several alleles at other QTL were associated with higher grain yields at selected field sites.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Large-area imaging reveals biologically driven non-random spatial patterns of corals at a remote reef - Clinton B. Edwards; Yoan Eynaud; Gareth J. Williams; Nicole E. Pedersen; Brian J. Zgliczynski; Arthur C. R. Gleason; Jennifer E. Smith; Stuart A. Sandin (Coral Reefs, 2017)

Genomic analysis of chimeric human cytomegalovirus vaccine candidates derived from strains Towne and Toledo - Nicolás M. Suárez; Betty Lau; George M. Kemble; Ronzo Lee; Edward S. Mocarski; Gavin W. G. Wilkinson; Stuart P. Adler; Michael A. McVoy; Andrew J. Davison (Virus Genes, 2017)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Blastocyst genotyping for quality control of mouse mutant archives: an ethical and economical approach - Ferdinando Scavizzi; Edward Ryder; Stuart Newman; Marcello Raspa; Diane Gleeson; Hannah Wardle-Jones; Lluis Montoliu; Almudena Fernandez; Marie-Laure Dessain; Vanessa Larrigaldie; Zuzana Khorshidi; Reetta Vuolteenaho; et al. (Transgenic Research, 2015)

The opioid receptor pharmacology of GSK1521498 compared to other ligands with differential effects on compulsive reward-related behaviours - Eamonn Kelly; Stuart J. Mundell; Anna Sava; Adelheid L. Roth; Antonio Felici; Kay Maltby; Pradeep J. Nathan; Edward T. Bullmore; Graeme Henderson (Psychopharmacology, 2015)

A reconstruction of extratropical Indo-Pacific sea-level pressure patterns during the Medieval Climate Anomaly - Ian D. Goodwin; Stuart Browning; Andrew M. Lorrey; Paul A. Mayewski; Steven J. Phipps; Nancy A. N. Bertler; Ross P. Edwards; Tim J. Cohen; Tas van Ommen; Mark Curran; Cameron Barr; J. Curt Stager (Climate Dynamics, 2014)

Rapid conversion of EUCOMM/KOMP-CSD alleles in mouse embryos using a cell-permeable Cre recombinase - Edward Ryder; Brendan Doe; Diane Gleeson; Richard Houghton; Priya Dalvi; Evelyn Grau; Bishoy Habib; Evelina Miklejewska; Stuart Newman; Debarati Sethi; Caroline Sinclair; Sapna Vyas; et al. (Transgenic Research, 2014)

Mechanisms for Eliminating Monoterpenes of Sagebrush by Specialist and Generalist Rabbits - Lisa A. Shipley; Edward M. Davis; Laura A. Felicetti; Stuart McLean; Jennifer Sorensen Forbey (Journal of Chemical Ecology, 2012)

Incorporating climate change adaptation into national conservation assessments - EDWARD T GAME; GEOFFREY LIPSETT‐MOORE; EARL SAXON; NATE PETERSON; STUART SHEPPARD (Global Change Biology, 2011)
The Convention on Biological Diversity requires that member nations establish protected area networks that are representative of the country's biodiversity. The identification of priority sites to achieve outstanding representation targets is typically accomplished through formal conservation assessments. However, representation in conservation assessments or gap analyses has largely been interpreted based on a static view of biodiversity. In a rapidly changing climate, the speed of changes in biodiversity distribution and abundance is causing us to rethink the viability of this approach. Here we describe three explicit strategies for climate change adaptation as part of national conservation assessments: conserving the geophysical stage, identifying and protecting climate refugia, and promoting cross‐environment connectivity. We demonstrate how these three approaches were integrated into a national terrestrial conservation assessment for Papua New Guinea, one of the most biodiverse countries on earth. Protected areas identified based on representing geophysical diversity were able to capture over 90% of the diversity in vegetation communities, suggesting they could help protect representative biodiversity regardless of changes in the distribution of species and communities. By including climate change refugia as part of the national conservation assessment, it was possible to substantially reduce the amount of environmental change expected to be experienced within protected areas, without increasing the overall cost of the protected area network. Explicitly considering environmental heterogeneity between adjacent areas resulted in protected area networks with over 40% more internal environmental connectivity. These three climate change adaptation strategies represent defensible ways to guide national conservation priority given the uncertainty that currently exists in our ability to predict climate changes and their impacts. Importantly, they are also consistent with data and expertise typically available during national conservation assessments, including in developing nations. This means that in the vast majority of countries, these strategies could be implemented immediately.

Low Temperature Geothermal Applications as Enablers of Sustainable Development: Practical Case Studies from Australia and UK - Edward Oldmeadow; Dora Marinova; David Birks; Steven Whittall; Stuart Brown (Water Resources Management, 2011)

Wastewater‐fed aquaculture in the East Kolkata Wetlands, India: anachronism or archetype for resilient ecocultures? - Stuart W. Bunting; Jules Pretty; Peter Edwards (Reviews in Aquaculture, 2010)
Wastewater‐fed aquaculture is generally in decline. The 12 500 ha East Kolkata Wetlands (EKW) Ramsar site in peri‐urban Kolkata, India, is the only large‐scale formal system still operating and appears to demonstrate a high degree of resilience. This paper identifies aspects of wastewater‐fed aquaculture in the EKW that contribute to its sustained operation. The Driving Forces, Pressures, State, Impact, Response (DPSIR) framework was used to structure the assessment. Resilience within the EKW can be attributed to the scale of operation, adaptive production strategies that optimise resource utilisation while minimising risks, self‐organisation among stakeholders and timely legislation and institutional interventions to preserve the natural character of the wetlands. The introduction of externalising technologies, erosion of social capital and loss of traditional ecological knowledge threaten to undermine this resilience. Outcomes from this analysis should inform future management of the EKW to ensure that resilience is retained and enhanced.

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Recovery of Aboveground Plant Biomass and Productivity After Fire in Mesic and Dry Black Spruce Forests of Interior Alaska - Michelle C. Mack; Kathleen K. Treseder; Kristen L. Manies; Jennifer W. Harden; Edward A. G. Schuur; Jason G. Vogel; James T. Randerson; F. Stuart Chapin (Ecosystems, 2008)

Asymmetric larval competition in the parasitoid wasp Nasonia vitripennis: a role in sex allocation? - Edward M. Sykes; Tabitha M. Innocent; Ido Pen; David M. Shuker; Stuart A. West (Behavioral Ecology and Sociobiology, 2008)

Asymmetric larval competition in the parasitoid wasp Nasonia vitripennis: a role in sex allocation? - Edward M. Sykes; Tabitha M. Innocent; Ido Pen; David M. Shuker; Stuart A. West (Behavioral Ecology and Sociobiology, 2007)

Indirect effects of algae on coral: algae‐mediated, microbe‐induced coral mortality - Jennifer E. Smith; Morrigan Shaw; Rob A. Edwards; David Obura; Olga Pantos; Enric Sala; Stuart A. Sandin; Steven Smriga; Mark Hatay; Forest L. Rohwer (Ecology Letters, 2006)
Declines in coral cover are generally associated with increases in the abundance of fleshy algae. In many cases, it remains unclear whether algae are responsible, directly or indirectly, for coral death or whether they simply settle on dead coral surfaces. Here, we show that algae can indirectly cause coral mortality by enhancing microbial activity via the release of dissolved compounds. When coral and algae were placed in chambers together but separated by a 0.02 μ m filter, corals suffered 100% mortality. With the addition of the broad‐spectrum antibiotic ampicillin, mortality was completely prevented. Physiological measurements showed complementary patterns of increasing coral stress with proximity to algae. Our results suggest that as human impacts increase and algae become more abundant on reefs a positive feedback loop may be created whereby compounds released by algae enhance microbial activity on live coral surfaces causing mortality of corals and further algal growth.

Agonistic behavior in naïve juvenile lobsters depleted of serotonin by 5,7-dihydroxytryptamine - Sarah B. Doernberg; Stuart I. Cromarty; Ralf Heinrich; Barbara S. Beltz; Edward A. Kravitz (Journal of Comparative Physiology A, 2001)

The controls on net ecosystem productivity along an Arctic transect: a model comparison with flux measurements - Mathew Williams; Werner Eugster; Edward B. Rastetter; Joseph P. Mcfadden; F. Stuart Chapin Iii (Global Change Biology, 2000)
Summary Assessments of carbon (C) fluxes in the Arctic require detailed data on both how and why these fluxes vary across the landscape. Such assessments are complicated because tundra vegetation has diverse structure and function at both local and regional scales. To investigate this diversity, the Arctic Flux Study has used the eddy covariance technique to generate ecosystem CO 2 ‐exchange data along a transect in northern Alaska. We use an extant process‐based model of the soil–plant–atmosphere continuum to make independent predictions of gross photosynthesis and foliar respiration at 9 of the sites along the transect, using data on local canopy structure and meteorology. We make two key assumptions: (i) soil respiration is constant throughout the flux measurement period, so that the diurnal cycle in CO 2 exchange is driven by canopy processes only (except at two sites where a soil respiration–temperature relationship was indicated in the data); and (ii) mosses and lichens play an insignificant role in ecosystem C exchange, even though in some locations their live biomass exceeds 300 g m −2 . We found that even with these assumptions the model could explain much of the dynamics of net ecosystem production (NEP) at sites with widely differing vegetation structure and moss/lichen cover. Errors were mostly associated with the predictions of maximum NEP; the likely cause of such discrepancies was (i) a mismatch between vegetation sampled for characterizing the canopy structure and that contained within the footprint of the eddy covariance flux measurements, or (ii) an increase in daytime soil and root respiration. Thus the model results tended to falsify our first assumption but not our second. We also note evidence for an actual reduction in NEP caused by water stress on warm, dry days at some sites. The model–flux comparison also suggests that photosynthesis may be less sensitive to low temperatures than leaf‐level gas‐exchange measurements have indicated.

Holocene river development and environmental change in Upper Wharfedale, Yorkshire Dales, England - Andy J. Howard; Mark G. Macklin; Stuart Black; Karen A. Hudson-Edwards (Journal of Quaternary Science, 2000)

A multiclass, multiresidue analytical method for pesticides in water - John F. Thompson; Stuart J. Reid; Edward J. Kantor (Archives of Environmental Contamination and Toxicology, 1977)